2011
DOI: 10.1098/rsta.2011.0181
|View full text |Cite
|
Sign up to set email alerts
|

The role of the international prototype of the kilogram after redefinition of the International System of Units

Abstract: Since 1889, the international prototype of the kilogram has served to define the unit of mass in what is now known as the International System of Units (SI). This definition, which continues to serve mass metrology well, is an anachronism for twenty-first century physics. Indeed, the kilogram will no doubt be redefined in terms of a physical constant, such as the Planck constant. As a practical matter, linking the quantum world to the macroscopic world of mass metrology has, and remains, challenging although g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In order to minimize serious consequences from such a hypothetical situation, CCM made its recommendations cited above [37]. A pertinent example that the change in definitions of the mole and kilogram will have no consequences in testing physical laws is provided by an experimental test of Einstein's mass-energy relation, as discussed in Appendix B of [55].…”
Section: Review Of Selected Papers and Summary Of Key Issues Raised Bmentioning
confidence: 99%
“…In order to minimize serious consequences from such a hypothetical situation, CCM made its recommendations cited above [37]. A pertinent example that the change in definitions of the mole and kilogram will have no consequences in testing physical laws is provided by an experimental test of Einstein's mass-energy relation, as discussed in Appendix B of [55].…”
Section: Review Of Selected Papers and Summary Of Key Issues Raised Bmentioning
confidence: 99%
“…The IPK and a group of the prototypes were inter‐compared originally around 1890, for the second time in 1948, and for the third time in 1990. By the third verification, it became obvious that the relative mass differences between the IPK, the témoins, and others were spreading over time even though the materials, storage, and usage were all similar, see Figure . Further, these relative differences suggested that the IPK itself was changing in mass by comparable or larger amounts; because except for its definition, it was just another cylinder of PtIr.…”
Section: Introductionmentioning
confidence: 97%
“…Although defining the kilogram by fixing the value of the Planck constant is conceptually more complex than, for example, defining the kilogram in terms of the mass of the electron or a specified atom, the other advantages of fixing the value of the Planck constant make this the preferable definition. See also the paper by Bordé [13], as well as those of Becker & Bettin [14], Stock [15] and Davis [16] in this issue.…”
Section: Choosing the Fundamental Constants To Be Used In The Definitmentioning
confidence: 99%